gamalieljacob91

5 Reputation

One Badge

7 years, 117 days

MaplePrimes Activity


These are questions asked by gamalieljacob91

hello, i have problem here.

> restart;
> with(linalg);
> NULL;
> fungsi1 := sum(d1[h]+b1[h], h = 1 .. 7);
> fungsi2 := sum(sum(d2[h, t]+b2[h, t], t = 1 .. 23), h = 1 .. 7);
> fungsi3 := sum(sum(d3[h, t]+b3[h, t], t = 1 .. 23), h = 1 .. 7);
> fungsi4 := sum(d4[k]+b4[k], k = 1 .. 3);
> fungsi := fungsi1+fungsi2+fungsi3+fungsi4;
> NULL;
> NULL;
> k1 := seq(sum(X[h, t], t = 1 .. 23) >= 9, h = 1 .. 6);
> k2 := seq(sum(Y[h, t], t = 1 .. 23) >= 2, h = 1 .. 6);
> k3 := seq(sum(Z[h, t], t = 1 .. 23) >= 2, h = 1 .. 6);
> NULL;
> k4 := seq(seq(X[h, t]+Y[h, t]+Z[h, t] <= 1, h = 1 .. 6), t = 1 .. 23);
> NULL;
> k5 := seq(seq(Z[h, t]+Z[h+1, t] <= 1, h = 1 .. 6), t = 1 .. 23);
> NULL;
> k6 := seq(sum(X[h, t]+Y[h, t]+Z[h, t], t = 1 .. 23) >= 5, h = 1 .. 7);
> k7 := seq(sum(X[h, t]+Y[h, t]+Z[h, t], t = 1 .. 23) <= 6, h = 1 .. 7);
> NULL;
> k8 := seq(sum(X[h, t], t = 1 .. 23)+b1[h]-d1[h] <= 15, h = 1 .. 6);
> k9 := seq(sum(Y[h, t], t = 1 .. 23)+b1[h]-d1[h] <= 4, h = 1 .. 6);
> k10 := seq(sum(Z[h, t], t = 1 .. 23)+b1[h]-d1[h] <= 4, h = 1 .. 6);
> NULL;
> k11 := seq(seq(Y[h, t]+Y[h+1, t]+b2[h, t]-d2[h, t] <= 1, t = 1 .. 23), h = 1 .. 6);
> NULL;
> k12 := seq(seq(Z[h, t]+Z[h+1, t]+b3[h, t]-d3[h, t] <= 1, t = 1 .. 23), h = 1 .. 6);
> NULL;
> k13 := sum(X[7, t], t = 1 .. 23)+b4[1]-d4[1] = 2;
> k14 := sum(Y[7, t], t = 1 .. 23)+b4[1]-d4[1] = 2;
> k15 := sum(Z[7, t], t = 1 .. 23)+b4[1]-d4[1] = 2;
> with(Optimization);
[ImportMPS, Interactive, LPSolve, LSSolve, Maximize, Minimize, 

  NLPSolve, QPSolve]
> CodeTools:-Usage(LPSolve(fungsi, {k1, k10, k11, k12, k13, k14, k15, k2, k3, k4, k5, k6, k7, k8, k9}, assume = {integer, nonnegative}));
Error, (in Optimization:-LPSolve) no feasible point found for LP subproblem

why it can be? please i need help. 

any idea for my problem?

 

> k1 := sum(X[h, t], t = 1 .. 23) >= 9;
9 <= X[h, 1] + X[h, 2] + X[h, 3] + X[h, 4] + X[h, 5] + X[h, 6]

   + X[h, 7] + X[h, 8] + X[h, 9] + X[h, 10] + X[h, 11] + X[h, 12]

   + X[h, 13] + X[h, 14] + X[h, 15] + X[h, 16] + X[h, 17]

   + X[h, 18] + X[h, 19] + X[h, 20] + X[h, 21] + X[h, 22]

   + X[h, 23], h = 1 .. 6

why 'h' still 'h'. from my textbooks the formula must be like this :
 

Page 1 of 1